Bystander suppression of experimental arthritis by nasal administration of a heat shock protein peptide. Issue 12 (12th September 2011) - Zonneveld-Huijssoon, Evelien; Roord, Sarah T A; de Jager, Wilco; Klein, Mark; Albani, Salvatore; Anderton, Stephen M; Kuis, Wietse; van Wijk, Femke; Prakken, Berent J
Abstract : Objectives: Mucosal immune therapy with disease-inducing antigens is an effective way to prevent experimental arthritis, but in humans these antigens are unknown. In juvenile idiopathic arthritis, however, T cell recognition of a so-called bystander antigen, heat shock protein 60 (HSP60), is associated with a good prognosis. Recently epitopes derived from HSP60, a microbial peptide (p1) and its self-homologue (p2) were reported to induce tolerogenic T cell responses in vitro in patients with arthritis. A study was undertaken to determine whether mucosal administration of these bystander epitopes can be similarly effective in suppressing arthritis. Methods: Rats were treated nasally with p1, p2 or phosphate-buffered saline before arthritis induction. Arthritis scores were assessed and peptide-specific proliferative responses, phenotypic analysis, cytokine production and in vitro suppressive capacity of cells were measured in lymph nodes and spleens. CD4 spleen T cells from p1- or p2-treated rats were adoptively transferred into naïve rats that were subsequently injected with complete Freund's adjuvant for arthritis induction. Results: Nasal administration of p1 prevented experimental arthritis whereas treatment with the self-homologue p2 did not. Adoptive transfer of CD4 T cells protected against experimental arthritis. Treatment with p1 increased peptide-specific and self-crossreactive interferon γ (IFNγ) production. Tumour necrosis factor α (TNFα) levels were reduced at the site of inflammation. Forkhead box P3 (FoxP3) expression remained stable but the suppressive capacity of T regulatory cells in p1-treated rats was enhanced. Conclusion: p1 immune therapy induces a population of CD4 T cells with reduced TNFα and increased peptide-specific IFNγ production at the site of inflammation. This population expresses FoxP3 and has potent suppressive capacity which, upon transfer, protects against arthritis. The bystander epitope p1 may therefore be a suitable candidate for antigen-specific immunotherapy in arthritis.